Analysis on the Reform of Physical Education Teaching in Medical Colleges From the Perspective of “Integration of Sports and Medicine” (Journal of Education and Development, 2022)
Through the method of literature review, this paper analyzes the social background of the integration of body and medicine, the advantages of the integration of body and medicine in medical colleges, and the reform ideas of physical education in medical colleges to practice the integration of body and medicine. It is considered that the practice of integration of sports and medicine should be based on medical colleges and give full play to the advantages of teachers and students in medical colleges, and the practice of integration of sports and medicine involves physical education teaching purposes, teaching contents, teaching methods, teaching process, teaching evaluation, physical education textbooks and other aspects.